Semantic Analysis of Nafs in the Qur’an: A Toshihiko Izutsu Perspective and Its Relevance in Modern Thought - Zaduna Fiddarain; Farrel Izham Prayitno; Sulhi Kholid Al Abid (Bulletin of Islamic Research, 2023)
This research aims to explore the concept of ‘nafs’ in the Qur'an, both historically and theologically, and understand its relevance in modern life. The research uses a descriptive-analytical qualitative approach, with syntagmatic and paradigmatic analyses of relevant Qur'anic verses, as well as classical and contemporary literature studies. The results show that ‘nafs’ covers the physical, moral, and spiritual dimensions of human beings, with the main classifications: nafs al-ammārah (a soul inclined to evil), nafs al-lawwāmah (a self-deprecating soul), and nafs al-mutma'innah (a serene soul). The transformation of the meaning of ‘nafs’ from the pre-Qur'anic to the post-Qur'anic period reflects the human journey towards purification of the soul (tazkiyah) which contributes to the formation of individual character and social harmony. In the modern context, the understanding of ‘nafs’ has significant relevance in education, Islamic psychology and individual moral development. The research concludes that the purification of the soul is central to the Qur'anic worldview, making the ‘nafs’ the centre of moral and spiritual responsibility, which has a direct impact on the justice and balance of society.